Into the newsroom [ exploring the digital production of regional television news - Hemmingway, Emma (Routledge, 2008)
This book explores how journalists and the digital technologies with which they are entangled construct television news at the micro level of practice. It challenges orthodox readings of television news production to explore fundamental questions concerning the ways in which we understand how journalists and technologies combine with one another in unpredictable ways in order to create news--from book's front page.